Portrait of Vince and Patricia Whiting at Coco Palms Chapel
Vince and Patricia Whiting holding hands in the entryway of the Coco Palms Chapel in Hawaii. They are celebrating their fourth wedding and twentieth wedding anniversary. Although the date on the verso of photograph states "1968," based on other photographs in the file the date is discerned as 1988.